Perhitungan Biaya Pengupasan dan Pengangkutan Overburden pada PIT 3000 Blok 12 PT Trubaindo Coal Mining - Liganic Saprudin; Agus Winarno; Henny Magdalena; Windhu Nugroho (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
In stripping overburden activities, calculate the costs in order to provide an overview of the costs that will be incurred by the company. The purpose is to provide an overview of the costs that will be incurred by the company. The results of the research that has been done are as follows with a target of overburden stripping target of 480,000 BCM, Productivity of Komatsu PC digging equipment 300 fleet 1 217.35 BCM/hour, Komatsu PC 300 fleet 2 digging tool productivity 226.22 BCM/hour and Komatsu PC 400 fleet 3 285.87 BCM/hour. Cost The cost of digging equipment ownership is Rp. 172,347/hour and the operational cost of digging equipment is Rp. 3,415,959/hour. The cost of ownership of the conveyance is Rp. 404,437/hour and the operational cost of the conveyance is Rp. 3,415,959/hour. operational costs Rp. 3,502,939 / hour. The company certainly incurs production costs. One of which is operational costs, therefore it is necessary to